Introduction to RF power amplifier design and simulation - Eroglu, Abdullah (Taylor & Francis, 2016)
Introduction to RF Power Amplifier Design and Simulation fills a gap in the existing literature by providing step-by-step guidance for the design of radio frequency (RF) power amplifiers, from analytical formulation to simulation, implementation, and measurement. Featuring numerous illustrations and examples of real-world engineering applications, this book:Gives an overview of intermodulation and elaborates on the difference between linear and nonlinear amplifiersDescribes the high-frequency model and transient characteristics of metal-oxide-semiconductor field-effect transistorsDetails activ